Time and Space Resolved First Order Optical Interference Between Distinguishable Photon Paths - Fernandez-Guasti, M.; García-Guerrero, C. (Frontiers in Physics, 2022)
Interference between different photons occurs and has been observed under diverse experimental conditions. A necessary condition in order to obtain interference fringes is the existence of at least two possible paths and unknown which-path information. If the photon beams have different frequencies, stability of the sources and fast spatially distributed detectors are required in order to detect the time displaced interference fringes. First order optical interference between two truly independent CW laser sources is observed. In contrast with the standard quantum criterion, interference is observed although the photon beams are distinguishable and, from quantum measurements, the path is unequivocally known for each photon beam. Segments of the continuous wave wavetrains are selected with an acousto-optic modulator. Temporal and spatial interference are integrated in a single combined phenomenon via streak camera detection. The displacement of the fringes in the time versus space interferograms evince the trajectories of the labeled photons. These results suggest that in non-degenerate frequency schemes, the ontology has to be refined and the which-path criterion must be precisely formulated. On the one hand, if the query refers to the frequency labeled photons, the path of each red or blue photon is known, whereas on the other hand, if the query is performed in terms of the detected photons, the path is unknown.